Exploring tutor-student interactions in a novel virtual design studio. (July 2021) - Nespoli, Oscar G.; Hurst, Ada; Gero, John S.
Abstract : This exploratory case study investigates a novel adaptation of the virtual studio pedagogy. Students are located in authentic professional practice settings, while tutors remain on campus. Verbalisations of tutors' and students' discussions in 13 weekly sessions were characterized and measured using topic modelling and FBS analysis. Tutors and students exhibited large differences: Tutors' cognitive behaviour was generally more abstract while the students' was more concrete. Further, while tutors were more concerned with design communication, students engaged with specific issues in the manufacturing and organizational setting of their host. Tutor-student interactions did not change significantly over time, with most of the interactions taking place in the solution space. Categorical differences in topics between tutors and students were found that remained consistent over time. Highlights: A novel virtual design studio pedagogy was created. Students were situated in a practice setting, while tutors remained on campus. Tutor-student interactions were characterized using topic analysis and FBS. Categorical differences in topics during interactions remained consistent over time. Tutors' cognitive behaviour was found to be more abstract than the students'.